2021
DOI: 10.1021/acs.jmedchem.0c01878
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Hydroxypyridinone APJ Receptor Agonist as a Clinical Candidate

Abstract: Apelin-13 is an endogenous peptidic agonist of the apelin receptor (APJ) receptor with the potential for improving cardiac function in heart failure patients. However, the low plasma stability of apelin-13 necessitates continuous intravenous infusion for therapeutic use. There are several approaches to increase the stability of apelin-13 including attachment of pharmacokinetic enhancing groups, stabilized peptides, and Fc-fusion approaches. We sought a small-molecule APJ receptor agonist approach to target a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…Tertiary benzyl amide 5 demonstrated a nearly 10-fold increase in potency relative to secondary amide 4 . Further leveraging the SAR developed in the oxadiazole series, we found that phenyl substitution with a p -chloro group utilizing an ethyl linker to the amide ( 6 ) led to a further 10-fold increase in potency. The constrained phenyl-substituted pyrrolidine amides 7a ( R isomer) and 7b ( S isomer) without any substitution provided a 5-fold potency improvement compared with 6 .…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Tertiary benzyl amide 5 demonstrated a nearly 10-fold increase in potency relative to secondary amide 4 . Further leveraging the SAR developed in the oxadiazole series, we found that phenyl substitution with a p -chloro group utilizing an ethyl linker to the amide ( 6 ) led to a further 10-fold increase in potency. The constrained phenyl-substituted pyrrolidine amides 7a ( R isomer) and 7b ( S isomer) without any substitution provided a 5-fold potency improvement compared with 6 .…”
mentioning
confidence: 97%
“…The APJ receptor plays a role in regulating cardiovascular functions involved in HF and is activated by its endogenous ligands apelin and elabela. Apelin is secreted as a 77 amino acid preproprotein and is rapidly cleaved to shorter biologically active fragments. Of those, (Pyr 1 )­apelin-13 peptide is the most abundant fragment in the myocardium and plasma and demonstrates strong binding affinity for the receptor ( h APJ K d = 4.5 nM) and functional activity ( h APJ EC 50 = 0.06 nM and r APJ EC 50 = 0.07 nM). Activation of the APJ receptor using (Pyr 1 )­apelin-13 improved cardiovascular function in HF animal models and clinically in HF r EF subjects. ,− Nevertheless, the therapeutic use of (Pyr 1 )­apelin-13 has been limited because of its plasma instability and the requirement of parenteral administration. , Significant effort has been made to identify orally active APJ agonists, including small molecules. AMG 986 (Figure ) was reported to improve stroke volume and EF in an acute rat model of diastolic dysfunction and was advanced to clinical trials. , …”
mentioning
confidence: 99%
See 3 more Smart Citations